Influence of delivery system on the efficacy of low concentrations of hydrogen peroxide in the disinfection of common healthcare-associated infection pathogens. Issue 1 (September 2020) - Amaeze, N.J.; Shareef, M.U.; Henriquez, F.L.; Williams, C.L.; Mackay, W.G.
Summary: Introduction: The ability of healthcare-associated infection pathogens to survive on environmental surfaces is well known. Disinfection is employed to reduce or remove these pathogens but disinfection failures still occur. One method with the potential to improve disinfection efficacy is whole-room disinfection with hydrogen peroxide (H2 O2 ). Aim: To determine the influence of delivery system on the efficacy of low-concentration H2 O2 on common healthcare-associated infection pathogens. Methods: SanoStatic (electrostatic spray) was compared with SanoFog (fogging) in terms of performance for delivery of 5% H2 O2 and trace silver ions for disinfection. The bacterial test challenges were vancomycin-resistant Enterobacterales (VRE), extended-spectrum β-lactamase (ESBL)-producing Klebsiella pneumoniae (ESBLK), carbapenemase-producing Enterobacterales (CPE), meticillin-resistant Staphylococcus aureus (MRSA), Clostridium difficile spores, Bacillus atropheus and Geobacillus stearothermophilus commercial spore strips. Findings: SanoFog and SanoStatic were effective when tested under the conditions of experimentation reported here. For VRE, ESBLK, CPE and MRSA, SanoFog and SanoStatic were comparable in performance. For C. difficile we concluded the following: SanoFog was most effective for disinfection of C. difficile spores when compared to SanoStatic. Conclusion: Whereas SanoFog and SanoStatic were effective against bacterial cells, the current practice of using SanoFog and SanoStatic together would be effective for disinfection of C. difficile spores based on investigations under the conditions of experimentation reported here. The spore strips results were not comparable to the results either for the vegetation cells (VRE, ESBLK, CPE, and MRSA) or for C. difficile spores.